INNOVATION MANAGEMENT IN THE SERVICE SECTOR: BEST PRACTICES AND EXPERIENCE OF LEADING COMPANIES (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
Innovative development in the service sector plays a key role in enhancing the competitiveness of companies in a rapidly changing business environment. This article discusses the importance of continuously monitoring change and adapting strategy to meet new challenges and opportunities. The main factors that emphasise the need for this approach are discussed, such as the dynamic market, customer needs, the competitive environment and technological advances. The authors suggest that continuous monitoring and adaptation of strategy helps companies to remain agile, innovative and competitive, ensuring successful development in the long term.